An overview of healthcare-associated Candida auris outbreaks in Ministry of Health hospitals-Saudi Arabia 2020-2022; Retrospective multicentric study. - Khalid H Alanazi; Hala M Roushdy; Waad I ALzubaidi; Arwa S Alanazi; Nawal M Alanazi; Ahlam H Alamri; Yahya I Alnshbah; Nawaf M Al Almatrafi; Zainah M Al Shahrani; Adel S Alanazi; Nasser H Alshanbari (PLoS ONE)
Background Candida auris (C. auris) is an emerging fungus pathogen associated with nosocomial infections that is seen as a serious global health issue. Aim To describe the epidemiology and features of hospital-acquired Candida auris outbreaks in the Ministry of Health hospitals (MOH). Methods A three-year (2020-2022) retrospective analysis of Candida auris outbreaks in the Saudi MOH hospitals. A total of 45 hospitals were involved, with 511 cases of Candida auris. The data collected from the General Directorate of Infection Prevention and Control (GDIPC) platform comprises all patients' data for C. auris instances, whether infected or colonized. Results Out of the 511 Candida auris recruited cases, 291 (56.9%) were infected, whereas 220 (43.1%) were colonized. 32.9% of cases were above the age of 65, and 68.9% were male. The majority of cases were admitted in the ICU unit (95.5%). Approximately 18.8% of cases were diabetes, and 18.5% were hypertensive. Central lines were discovered in 37.7% of the cases. Approximately 85.9% of cases had Foley catheters, 68.5% were on ventilators, and 53.8% had a tracheostomy. The crude mortality rate was particularly high (41.5%) among the study cases. It was non-significantly higher among infected individuals (44.7%) than colonized patients (37.3%) at (p value = 0.093). The prevalence of hypertension (p = 0.001), DM (p = 0.003), and peripheral line insertion (p = 0.004) was significantly higher among colonized patients. While the presence of COVID-19 (p = 0.001), and central line insertion (p = 0.001) was significantly higher among infected patients. Conclusion C. auris is a new pathogen that causes hospital outbreaks. Strict adherence to infection prevention and control criteria established by the Centre for Disease Control (CDC) and GDPIC has significantly contained and reduced the spread of these outbreaks. One-month retrospective surveillance before diagnosing the index case and a prospective surveillance strategy for at least three months is highly recommended.